Wavelets, Evolution of Some Ideas and Applications - Ortiz Fernández, Alejandro (2019)
In this writing, we present a brief overview of wavelets theory, a theory that has had great success in applications to various areas of science and technology. This article aims to inform about some wavelets ideas, as well as some of its applications.